Health, Gender and Media - Rojas, Ángela María; Vargas Trujillo, Elvia (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This article describes the role of media in the construction of gender identities and the implications of these processes in health and wellness. The purpose is to educate people working in the media on the effect of exposure to messages transmitted in the construction of gender identities. Evidence on the relationship between cognitive gender, health and welfare of women and men are presented as well as some reflections on the importance of considering gender in creative processes, development and production of media messages.